STUDY OF MORPHOLOGICAL CHANGES IN THE SMALL INTESTINAL WALL OF 3-MONTH-OLD WHITE-BORN MICE UNDER THE INFLUENCE OF LOW CONCENTRATION ACETIC ACID (Scientific Conference on Multidisciplinary Studies, 2025)
Actively ongoing research into chemical burns of the gastrointestinal tract confirms the complexity and relevance of this problem. According to the American Association of Poison Control Centers, in 2008 alone, more than 1.6 million children were poisoned, with alkaline esophageal burns occurring in 18-46% of cases after ingestion of various household chemicals.